2023
DOI: 10.1021/acs.inorgchem.3c02371
|View full text |Cite
|
Sign up to set email alerts
|

4-Oxo-7-fluoro-1,10-phenanthroline-2,9-diamides: Synthesis, Structural Features, Lanthanide Complexes, and Am(III)/Ln(III) Solvent Extraction

Nane A. Avagyan,
Pavel S. Lemport,
Vitaly A. Roznyatovsky
et al.

Abstract: A highly efficient synthetic approach was developed for the synthesis of unsymmetrical 1,10-phenanthroline-2,9-diamides with two different substituents in the fourth and seventh positions of the phenanthroline core. The structures of these ligands were confirmed using various spectral methods including 2D-NMR and X-ray analysis. Quantum chemical calculations supported the presence of tautomeric forms of these ligands. Furthermore, it was discovered that these compounds exhibit polydentate ligand behavior towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…In our previous studies, 35,36 we showed that both symmetric 4,7-difluoro-phenanthrolinediamides 1 and asymmetric 4-oxo-7-fluoro-phenanthrolinediamides 2 can be obtained from the 4,7-dichloride precursor 3 (Scheme 1). 36 However, an attempt to obtain fluoro-oxo diamide 2 by fluorination of chloro-oxo diamide 4 was unsuccessful.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous studies, 35,36 we showed that both symmetric 4,7-difluoro-phenanthrolinediamides 1 and asymmetric 4-oxo-7-fluoro-phenanthrolinediamides 2 can be obtained from the 4,7-dichloride precursor 3 (Scheme 1). 36 However, an attempt to obtain fluoro-oxo diamide 2 by fluorination of chloro-oxo diamide 4 was unsuccessful.…”
Section: Resultsmentioning
confidence: 95%
“…We have already observed this phenomenon earlier and discussed it in detail in one of our previous papers. 36 Complete hydrolysis of both halide atoms at positions 4 and 7 should lead to the formation of molecules with an even greater number of tautomeric forms. We carried out quantum chemical calculations, which showed that the most energetically advantageous form in this case is the oxo-hydroxy form in comparison with the dihydroxy and dioxo forms (Fig.…”
Section: Preparation Of Oxo-hydroxy-phenanthrolinediamidesmentioning
confidence: 99%
“…Among N-,O-donor ligands, phenanthroline and bipyridine ligands have been proposed as promising candidates to provide extraction features 19–21 and well-defined structure–property relationships. 22–24…”
Section: Introductionmentioning
confidence: 99%